“Cultural Universe”: slavery, freedom and mobility in Minas Gerais. (Ágora Journal, 2024)
Book review: PAIVA, Eduardo França. “For my work, service and industry”: stories of Africans, Creoles and mixed race people in the mines, 1716-1789. Belo Horizonte: Caravan, 2022. 438p.
Keywords: History of Brazil; 18th century; Minas Gerais; Slavery.